APPLICATION EFFECT OF HAND MIXER AND OVERHEAD MIXER ON MIXING PERFORMANCE FOR THE MANUFACTURE OF ARTIFICIAL LEATHER - Dewi Nurhidayati (Politek ATK Yogyakarta Press, 2023)
The mixing process is necessary for the manufacture of a product, one of which is the manufacturing process of artificial leather. The mixing process in the manufacture of artificial leather aims to mix raw materials and additives such as fillers, stabilizers, plasticizers, and others. The mixing process is carried out using a mixer. This study aims to determine the effect of using mixers that have different specifications. The mixer used is the Hand Mixer Miyako SM-625 with the Overhead Mixer IK RW 20. Both of these mixers have differences in speed and type of agitator.From the results of organoleptic test, both of these mixers there was no difference. But the results of the physical test showed that the values of tensile strength, elongation, and tear strength were higher when using the IK RW 20 Overhead Mixer. This indicated that both mixers could be used in the manufacture of artificial leather, but to obtain measurable test results, using the IK RW 20 Overhead Mixer was recommended, seen from the difference in each of the physical test parameters.